Pengembangan Abon Ikan Kembung dan Kerang Hijau sebagai Alternatif Lauk Tinggi Protein dan Zat Besi: The Development of Mackerel Fish and Green Mussels Floss as an Alternative High Protein and Iron Side Dish - Safitri, Indira Nur; Marliyati, Sri Anna; Nasution, Zuraidah (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2025)
Green mussel is a food ingredient rich in nutrients and widely known by the general public due to its affordable price and easy accessibility. Mackerel fish floss with the substitution of green mussel is one alternative dish that can help improve the provision of protein and iron for women of reproductive age. This research aims to develop and analyze the nutritional content of the floss product based on mussels. The study used three different formulations with varying ratios of mackerel fish and green mussel: F0(100:0), F1(80:20), and F2(60:40). Based on organoleptic tests, physical characteristics, and nutritional content analysis, F2 was determined as the selected formula. The selected formulation of the floss contains 8.93% moisture content, 6.04% ash content, 34.91% protein, 27.85% fat, 22.27% carbohydrates, and 8.17 mg of iron. A serving size of the mackerel fish floss with green mussel substitution, equivalent to 1 tablespoon, contributes 72 kcal (3.2-3,5%) of daily energy for woman of reproductive age. The selected formulation of mackerel fish and green mussels floss meets the criteria to claim it as a high-protein and iron product.